APLIKASI EDUKASI PENGENALAN RENTAL MOBIL DI BATAM MENGGUNAKAN AUGEMENTED REALITY BERBASIS ANDROID - Rahfy, Rahfy; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2021)
Education example in media promotion of car rental services. The application of this education has a purpose where in its application the public can use car rental services and easily determine the car they want to use. Augmented Reality is an interaction that combines virtual objects into two dimensions or three dimensions which are then combined together so as to create a mix between realistic and virtual. Augmented reality is a multimedia that connects mobile devices as a means of taking pictures or objects and converting them into the form of applications that describe real situations or called 3D. Android is a Linux-based operating system that has been developed by the Open Handset Alliance such as software, hardware, and providers on Google, HTC, Intel, Motorola, Qualcomm, and T-Mobile which have the advantage of completeness of available applications. Carrying out an activity such as offering a car rental service is not easy because there is so much competition in the world. In this way there is still no significant improvement and less attractive